Legislation on Halal Food in Pakistan: An Analytical Study - Sabreen, Mudasra (Journal of Islamic and Religious Studies, 2021)
The term ‘ḥalāl ’ signifies ‘permissible’ for Muslims. Islamic laws regarding the determination of ḥalāl and harām food have been clear but after the introduction of modern techniques of food deciding of food as ḥalāl or harām has become a major concern for Muslim populations as well as Muslim states. Muslim states have introduced laws to ensure ḥalāl character of foods and Pakistan is no exception. In Pakistan, there are several laws related to this issue. The West Pakistan Pure Food Ordinance was enacted in 1960 which regulated the preparation and sale of foods. The Breastfeeding Ordinance 2002 was introduced to regulate baby food manufacture. Then there are laws like Pakistan Status of Food Laws and Regulations 2015, the Halal Food Authority Act 2015, and Pakistan Hotel and Restaurants Act 1976. With time, the need was felt to establish bodies which can verify food ingredients as well as manufacture procedure and can issue certificates. There is a need to thoroughly analyze these laws as well as the procedure of ḥalāl certification to find out the strengths and flaws/lacunas of the system if any. This article will present an analytical study of laws related to ḥalāl food in Pakistan and will propose suggestions to improve the effectiveness of these laws.